Speculations 3 - Austin, Michael; Gironi, Fabio; Jackson, Robert; Ennis, Paul J.; Gokey, Thomas (punctum books, 2012)
In this third volume of Speculations, a serial imprint created to explore post-continental philosophy and speculative realism, a wide range of topics are covered, from the philosophy of religion to psychoanalysis to the philosophy of science to gender studies, and in a wide variety of formats (articles, interviews, position pieces, translations, and review essays).